Multiprotocol lambda switching combining MPLS traffic engineeringcontrol with optical crossconnects. - Awduche, D. (IEEE Communications magazine)
This article describes an approach to the design of control planes for optical crossconnects which leverages existing control plane techniques developed for MPLS traffic engineering. The proposed approach combines recent advances in MPLS traffic engineering control plane constructs with OXC technology to provide a framework for real-time provisioning of optical channels, foster development and deployment of a new class of OXCs, and allow the use of uniform semantics for network management and operations control in hybrid networks consisting of OXCs and label switching routers. The proposed approach is particularly advantageous for OXCs intended for data-centric optical internetworking systems